Uji Aktivitas Antioksidan Ekstrak Etanol Kulit Batang Kemiri (Aleurites moluccana L.) Dengan Metode DPPH (1,1-Diphenyl-2-Picrylhidrazyl): Uji Aktivitas Antioksidan Ekstrak Etanol Kulit Batang Kemiri (Aleurites moluccana L.) Dengan Metode DPPH (1,1-Diphenyl-2-Picrylhidrazyl) - -, Keyman; -, Ridwan (Universitas Muslim Buton, 2022)
Candlenut bark is a source of various bioactive compounds with antioxidant potential and or free radical neutralization. This study investigated the antioxidant activity of candlenut bark extract. The research was carried out through several stages including: sample preparation, sample extraction, making reagents, making ethanol extracts, making vitamin C solutions, measuring the maximum wavelength of DPPH, and measuring the absorbance of free radical neutralization using the DPPH method. The results showed that the ethanol extract of candlenut stems had antioxidant activity as indicated by the higher the volume of ethanol extract added to the test solution, the higher the percentage of free radical neutralization. The ratio of the volume with the percentage of free radical neutralization, which is 10 mg/mL has a free radical neutralization percentage of 8.90%, 25 mg/mL has a neutralization percentage of 26.03%, 50 mg/mL has a neutralization percentage of 44.52%, and 75 mg/mL has a neutralization percentage of 65.75%.